2020
DOI: 10.1186/s13578-020-0377-9
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PI3 kinase association improves the sensitivity of secondary mutation of KIT to Imatinib

Abstract: Background: KIT mutations are the predominant driver mutations in gastrointestinal stromal tumors (GISTs), and targeted therapy against KIT has improved treatment outcome dramatically. However, gaining secondary mutation of KIT confers drug resistance of GISTs leading to treatment failure. Results: In this study, we found that secondary mutation of KIT dramatically increases the ligand-independent activation of the receptor and their resistance to the often used KIT inhibitor Imatinib in the treatment of GISTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…Oncogenic KIT mutations often occur in malignancies such as GISTs and mastocytosis [ 3 , 7 ], and our previous studies suggested that KIT mutants mediated distinct signaling pathways in addition to the ligand-independent activation [ [20] , [21] , [22] ]. In order to know whether PTPRE attenuates the activation of KIT mutants similarly as wild-type KIT, we further studied the function of PTPRE on the activation of KIT mutation D816V which is the most often happened mutation in mastocytosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oncogenic KIT mutations often occur in malignancies such as GISTs and mastocytosis [ 3 , 7 ], and our previous studies suggested that KIT mutants mediated distinct signaling pathways in addition to the ligand-independent activation [ [20] , [21] , [22] ]. In order to know whether PTPRE attenuates the activation of KIT mutants similarly as wild-type KIT, we further studied the function of PTPRE on the activation of KIT mutation D816V which is the most often happened mutation in mastocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…KIT is a receptor tyrosine kinase that plays an important role in hematopoiesis, gametogenesis and melanogensis, and oncogenic KIT mutations have been identified in GISTs, mastocytosis, acute myeloid leukemia, melanoma and others [ [1] , [2] , [3] , 7 , 23 , 24 ]. Signaling studies of wild-type KIT and KIT mutants have showed that KIT mutants have different signaling properties in addition to the ligand independent activation which was considered as the main cause of cell transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To produce Ba/F3 cells expressing KIT and either DDR1 or DDR2, EcoPack cells were transfected with either pMSCVneo/DDR1 or pMSCVneo/DDR2 using lipofectamine 2000 in accordance with the manufacturer's instructions. Supernatants were harvested 48 h after transfection and were used to infect Ba/F3 cells expressing either wild‐type KIT or KIT mutants previously established 24 . After selection with 1 mg/mL neomycin for 2 weeks, the expression of DDR1 or DDR2 was examined by western blot analysis.…”
Section: Materials and Medthodsmentioning
confidence: 99%
“…Gain-of-function mutations of KIT have been identified in around 80% of gastrointestinal stromal tumors (GISTs) (Tarn et al, 2005;Steigen et al, 2007;Zhu et al, 2020) and mastocytosis (Nagata et al, 1995;Longley et al, 1999), and to a lesser extent in acute myeloid leukemia (Boissel et al, 2006) and germ cell tumors (Looijenga et al, 2003). Among all the mutations, D816V mutation in exon 17 of KIT is the most often occurred mutation which accounts for around 70% of mastocytosis but it is rarely found in GISTs.…”
Section: Introductionmentioning
confidence: 99%